The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3856/vol41-issue4-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive aspects of the caridean shrimp Atya scabra (Leach, 1815) (Decapoda: Atyidae) in Sao Sebastiao Island, southwestern Atlantic, Brazil

Abstract: ABSTRACT. The caridean freshwater shrimp Atya scabra is a common resident of stream systems of tropical rainforests in America, including Brazilian drainages. This shrimp has an amphidromous life cycle, which increases its vulnerability when facing habitat fragmentation. Since information on the reproduction of this species is still limited, we present here data on egg production, egg loss, and energy investment, to achieve a better understanding of reproductive features of A. scabra. Specimens were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
6
1
1
Order By: Relevance
“…The number of individuals sampled in this study (N = 233) is low when compared to a study by Almeida et al (2010) (N = 3752) in Bahia, but higher than that reported by Herrera-Correal et al (2013) (N = 74) in São Paulo, both of which were carried out in Brazil. The difference in the number of individuals sampled may be related mainly to the methodology (sampling period and methods) and the geological characteristics of the river being sampling.…”
Section: Population Biologycontrasting
confidence: 68%
“…The number of individuals sampled in this study (N = 233) is low when compared to a study by Almeida et al (2010) (N = 3752) in Bahia, but higher than that reported by Herrera-Correal et al (2013) (N = 74) in São Paulo, both of which were carried out in Brazil. The difference in the number of individuals sampled may be related mainly to the methodology (sampling period and methods) and the geological characteristics of the river being sampling.…”
Section: Population Biologycontrasting
confidence: 68%
“…increases with female size in caridean shrimps, decapods, and crustaceans in general (e.g. Reid and Corey 1991, Anger and Moreira 1998, Correa and Thiel 2003, Lara and Wehrtmann 2009, Tamburus et al 2012, Herrera-Correal et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, here we report the first RO value for any pontoniine species (Table 2). The RO of Periclimenes rathbunae females (0.24) was higher than that reported for some free-living marine shrimps: 14.4 ± 2.5% for Palaemon northropi (Rankin, 1898) (see Anger and Moreira 1998) and 17.8 ± 6.0% for Heterocarpus vicarius Faxon, 1893 (see Echeverría-Sáenz and Wehrtmann 2011); and freshwater shrimps: 18.6 ± 3.0% for Palaemon pandaliformis (Stimpson, 1871) (see Anger and Moreira 1998), 19.1 ± 4.5% for Macrobrachium acanthurus (Wiegmann, 1836) (see Anger and Moreira 1998), 21.7 ± 6.6% for Macrobrachium olfersii (Wiegmann, 1836) (see Anger and Moreira 1998), and 3.6 ± 1.9% for Atya scabra (Leach, 1816) (see Herrera-Correal et al 2013). These results suggest that marine caridean shrimps species living in association with other invertebrates are able to invest on average more energy in brood production than free-living species.…”
Section: Discussionmentioning
confidence: 99%